(untitled) (Colombia Medica, 2015)
Objective:The main purpose of this study was to describe a group of Colombian physical therapists’ beliefs and attitudes towards Evidence-Based Practice (EBP), their education, knowledge and skills for implementing EBP, the use of relevant literature in clinical practice, access to and availability of scientific information and perceived barriers to including EBP in practice. Methods:This was a cross-sectional study which involved 1,064 Colombian physical therapists. The study used a 50-item screening questionnaire EBP developed to estimate attitudes, beliefs, knowledge and skills regarding. This instrument has been adapted and was validated previously in Colombia by Flórez-López et al. Results:The population mostly consisted of young females (77.2%) aged 22 to 29 years old (79.4%). Most respondents had an undergraduate degree (87.7%). The physical therapists stated that they had positive attitudes and beliefs regarding EBP, most of them answering that they agreed or strongly agreed that EBP is necessary (71.6%), the relevant literature is useful for practice (61.3%), EBP improves the quality of patient care (64.1%) and evidence helps in decision-making (44.5%). Forty-one percent of the respondents indicated that a lack of research skills was the most important barrier to the use of evidence in practice. Conclusion:The physical therapists reported that they had a positive attitude to EBP and were interested in learning about or improving the skills necessary to adopt EBP in their clinical practice.